Shine-Dalgarno Sequences Play an Essential Role in the Translation of Plastid mRNAs in Tobacco. Issue 12 (13th November 2017) - Scharff, Lars B.; Ehrnthaler, Miriam; Janowski, Marcin; Childs, Liam H.; Hasse, Claudia; Gremmels, Jürgen; Ruf, Stephanie; Zoschke, Reimo; Bock, Ralph
Abstract : Genome-wide analysis sheds light on the dependence of plastid translation on interactions between Shine-Dalgarno-like sequences in mRNA and the anti-Shine-Dalgarno sequence in 16S ribosomal RNA. Abstract: In prokaryotic systems, the translation initiation of many, though not all, mRNAs depends on interaction between a sequence element upstream of the start codon (the Shine-Dalgarno sequence [SD]) and a complementary sequence in the 3′ end of the 16S rRNA (anti-Shine-Dalgarno sequence [aSD]). Although many chloroplast mRNAs harbor putative SDs in their 5′ untranslated regions and the aSD displays strong conservation, the functional relevance of SD-aSD interactions in plastid translation is unclear. Here, by generating transplastomic tobacco ( Nicotiana tabacum ) mutants with point mutations in the aSD coupled with genome-wide analysis of translation by ribosome profiling, we provide a global picture of SD-dependent translation in plastids. We observed a pronounced correlation between weakened predicted SD-aSD interactions and reduced translation efficiency. However, multiple lines of evidence suggest that the strength of the SD-aSD interaction is not the only determinant of the translational output of many plastid mRNAs. Finally, the translation efficiency of mRNAs with strong secondary structures around the start codon is more dependent on the SD-aSD interaction than weakly structured mRNAs. Thus, our data reveal the importance of the aSD in plastid translation initiation, uncover chloroplast genes whose translation is influenced by SD-aSD interactions, and provide insights into determinants of translation efficiency in plastids.